Incipient heat damage in carbon fibre reinforced composites - Wong, Ledon Chien Hern. (2013)
This study highlighted a recent trend of increasing usage of Polymer Matrix Composite (PMC) materials in aircraft structures in the Aviation industry. Commercial aircraft Original Equipment Manufacturers (OEM) such as Airbus and Boeing are leveraging on the advantages composite materials possess to increase fuel efficiency and hence reduce operating and maintenance costs.